Pengaruh Motivasi Belajar Dan Self Efficiacy Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Metodologi Penelitian - Julia Risky Handayani; Marsofiyati Marsofiyati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research is motivated by the importance of educational quality which is influenced by internal and external factors in learning achievement. Motivation drives students to achieve academic goals, while self-efficacy strengthens self-confidence and perseverance in facing challenges. With the global challenges facing education in Indonesia, analysis of these factors is crucial. The purpose of this study is to analyze the effect of learning motivation and self-efficacy on student learning outcomes. This study uses associative research with a quantitative approach, through a survey research method by distributing questionnaires to students of the Office Administration Education Study Program class of 2022 at the State University of Jakarta as the population in this study. With a sample of 41 students from classes A and B who meet the criteria for filling out the questionnaire, then the data was analyzed using SPSS version 30.0.0.0. The results of this study indicate that learning motivation and self-efficacy have a positive and significant effect on student learning outcomes. Partially, students who have high motivation and self-confidence tend to get better learning outcomes. The implication of the results of this study is that lecturers and educational institutions need to pay attention to increasing students' motivation and self-efficacy through teaching methods and programs that support and can increase their academic self-confidence, thereby optimizing learning outcomes and the quality of graduates.